Johannes Freinsheim. Supplementa in Q. Curtium Supplemente zu Q. Curtius - Siemoneit, Gabriel (Holzhausen, 2019)
Johann Freinsheim's Supplementa in Q. Curtium are supplements to the lost parts of the Historiae Alexandri, an ancient history of Alexander the Great written by Q. Curtius Rufus. For the first time, a modern edition and a complete German translation along with Freinsheim's copious references is made available.